Simulation on solidification of an Al-Ni alloy under electromagnetic stirring - Sha Minghong; Wang Tongmin; Bai Fudong (China Foundry, 2012)
The microstructure of Al-Ni alloy has a significant influence on its performance, while electromagnetic stirring is one of the most effective methods for control of solidification structure of Al alloy. To investigate the effect of electromagnetic stirring on the solidification of the ingot, the solidification of the Al-50Ni alloy in vacuum with electromagnetic stirring was described by numerical simulation in this paper; and a three dimensional mathematical model was established. The electromagnetic field was simulated by ANSYS software and the thermal-flow field was simulated by FLUENT software. The coupling between the electromagnetic field and the thermal-flow field was implemented by user-defined subroutines. It is found that the current intensity has significant influences on the fluid flow and the microstructure of the alloy. The simulation results agree well with the experimental results, and the optimum current intensity under the exprimental conditions is 80 A, while the frequency is 50 Hz.